Capturing Camelot : Stanley Tretick's Iconic Images of the Kennedys - Kelley, Kitty (New York Martin Press, 2012)
When Kennedy took office, Stanley Tretick was given extensive access to the White House, and the picture magazine "Look" hired him to cover the president and his family. This collection includes some of the most memorable images of America's Camelot and evokes the uniquely hopeful historical era from which it emerged.
Include Color Illustration
Keywords: Photographers -- Portrait photography -- United States